New means of financing international needs - Steinberg, Eleanor B.; Yager, Joseph A.; Brannon, Gerard Marion; Brookings Institution (Washington : Brookings Institution, 1978)
This book examines the means of raising money for international purpose. After examining a wide range of possibilities, the authors selected three for intensive analysis: taxes on trade and on certain other international transactions; charges on polluters of the marine environment; and revenues from the exploitation of nonliving ocean resources. It also highlighted some of the problems and possible solutions.
Includes index.
Includes bibliographical references
usc 06/06/18
Loans
Keywords: Finance; International agencies; International finance; Developing countries